Systematics of the Trichoderma harzianum species complex and the re-identification of commercial biocontrol strains - Chaverri, Priscila; Branco-Rocha, Fabiano; Jaklitsch, Walter; Gazis, Romina; Degenkolb, Thomas; Samuels, Gary J. (Mycologia, 2015)
Trichoderma harzianum is known as a cosmopolitan, ubiquitous species associated with a wide variety of substrates. It is possibly the most commonly used name in agricultural applications involving Trichoderma, including biological control of plant diseases. While various studies have suggested that T. harzianum is a species complex, only a few cryptic species are named. In the present study the taxonomy of the T. harzianum species complex is revised to include at least 14 species. Previously named species included in the complex are T. guizhouense, T. harzianum, and T. inhamatum. Two new combinations are proposed, T. lentiforme and T. lixii. Nine species are described as new, T. afarasin, T. afroharzianum, T. atrobrunneum, T. camerunense, T. endophyticum, T. neotropicale, T. pyramidale, T. rifaii and T. simmonsii. We isolated Trichoderma cultures from four commercial biocontrol products reported to contain T. harzianum. None of the biocontrol strains were identified as T. harzianum s. str. In addition, the widely applied culture 'T. harzianum T22' was determined to be T. afroharzianum. Some species in the T. harzianum complex appear to be exclusively endophytic, while others were only isolated from soil. Sexual states are rare. Descriptions and illustrations are provided. A secondary barcode, nuc translation elongation factor 1-α (TEF1) is needed to identify species in this complex.